Acute otitis media. Issue 4 (July 2015) - Atkinson, Helen; Wallis, Sebastian; Coatesworth, Andrew P
Abstract: Acute otitis media (AOM) is a common problem facing general practitioners, paediatricians and otolaryngologists. This article reviews the aetiopathogenesis, epidemiology, presentation, natural history, complications and management of AOM. The literature was reviewed by using the PubMed search engine and entering a combination of terms including 'AOM', 'epidemiology' and 'management'. Relevant articles were identified and examined for content. What is the take-home message? AOM is a very common problem affecting the majority of children at least once and places a large burden on health care systems throughout the world. Although symptomatic relief is often enough for most children, more severe and protracted cases require treatment with antibiotics, especially in younger children.